2017
DOI: 10.1016/j.immuni.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Are Crucial for Induction of Group 2 Innate Lymphoid Cells and Clearance of Helminth Infections

Abstract: Mast cells are important for eradication of intestinal nematodes; however, their precise mechanisms of action have remained elusive, especially in the early phase of infection. We found that Spi-B-deficient mice had increased numbers of mast cells and rapidly expelled the Heligmosomoides polygyrus (Hp) nematode. This was accompanied by induction of interleukin-13 (IL-13)-producing group 2 innate lymphoid cells (ILC2) and goblet cell hyperplasia. Immediately after Hp infection, mast cells were rapidly activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
144
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 47 publications
6
144
0
Order By: Relevance
“…43,44 It belongs to the IL-1 family of cytokines and is thus translated in a proform that can be further processed. However, in contrast to IL-1b and IL-18, IL-33 is biologically active before cleavage and can localize to the nucleus where it binds chromatin, which is augmented upon T. spiralis infection.…”
Section: Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 It belongs to the IL-1 family of cytokines and is thus translated in a proform that can be further processed. However, in contrast to IL-1b and IL-18, IL-33 is biologically active before cleavage and can localize to the nucleus where it binds chromatin, which is augmented upon T. spiralis infection.…”
Section: Transmissionmentioning
confidence: 99%
“…Interestingly, a recent study also found that mast cells not only can respond to IL-33 but might also enhance the transmission of type 2 signals by the production of IL-33 in response to adenosine triphosphate release by dying epithelial cells. 44 …”
Section: Transmissionmentioning
confidence: 99%
“…To date, the contributions of ILC2s to host-protective responses in the context of other helminths are less defined. A recent study by Shimokawa et al has shown that mast cells cooperate with ILC2s to promote immunity to H. polygyrus (53). Specifically, they reported that ATP-activated mast cells promote ILC2 responses via their secretion of IL-33 and that these events contribute to reduced parasite burdens (53).…”
Section: Innate Immunitymentioning
confidence: 99%
“…A recent study by Shimokawa et al has shown that mast cells cooperate with ILC2s to promote immunity to H. polygyrus (53). Specifically, they reported that ATP-activated mast cells promote ILC2 responses via their secretion of IL-33 and that these events contribute to reduced parasite burdens (53). Additional studies report that ILC2s promote the differentiation of T H 2 cells following H. polygyrus infection via their secretion of IL-4(54), and preliminary reports suggest that ILC2s may contribute to host-protective responses against Strongyloides venezuelensis , T. muris and Schistosoma species(5557).…”
Section: Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation